Evaluación de la eficiencia en el desempeño laboral de los servidores públicos administrativos del Distrito de Educación 13D12 Tosagua-Rocafuerte, periodo 2021-2022 - Carranza Almeida, Darlyn Fabricio (2023)
The present research work was carried out with the purpose of evaluating the efficiency of the work performance of public officials of the Education District 13D12 Tosagua-Rocafuerte, period 2021-2022. For this, it was necessary to apply investigative methods such as deductive, inductive and analytical-synthetic, by which reliable data could be collected from the proven facts. This consists of three methodological phases where, phase 1, the main functions performed by public officials were identified, through field research and technical visits for the application of an interview with the director of the District, resulting in the with nine departments, which respond to their activities individually. In phase 2, a survey was applied, resulting in the levels of efficiency of the work performance of each of the institution's collaborators, identifying that there are insufficient personnel, which leads to delays in the processes. execution. In phase 3, the proposal for an improvement action plan was made, which is focused on mitigating the main problems that the institution has. Therefore, through the application of the aforementioned improvement action plan, it will be possible to propose actions and strategies necessary to solve such needs and thus achieve labor efficiency in the institution.